Thermal actuation performance modification of coiled artificial muscle by controlling annealing stress. Issue 5 (30th November 2017) - Li, Te; Wang, Yongqing; Liu, Kuo; Liu, Haibo; Zhang, Jiali; Sheng, Xianjun; Guo, Dongming
ABSTRACT: Twisted and coiled polymer (TCP) is a promising linear artificial muscle fabricated from nylon or other polymeric fibers, whose geometric structure is similar to a coil spring. TCP muscle is actuated reversibly with negative coefficients of thermal expansion. Twisting, coiling, and annealing are the main fabricating procedures. Annealing is the key process to form TCP muscles with stable performance. To modify and enhance actuation performance, it is necessary to explore and reveal influences of annealing process on thermal actuation (contraction strain, nominal modulus, and geometrical characteristic). Therefore, a new TCP fabrication and test platform is first established, which can quantize key geometrical and force parameters by multiple precise sensors. Then, four types of TCP muscles using nylon 6 fibers with varied diameters are fabricated and annealed under different conditions. As one of the important factors in annealing process, the nominal tensile stress is adjusted and controlled. Meanwhile, the contraction strain and nominal modulus are tested compared with the general annealing method. Finally, the experiment results show that contraction strain can be enhanced about two times (nominal modulus decreases accordingly) by increasing annealing stress, and the actuation performance can be remodeled reversibly by adjusting annealing stress and annealing repetitively. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 383–390 Abstract : Soft twisting and coiling polymer muscles from nylon fiber (fishing line) can be remodeled by repetitive annealing under different stress loads, which means that the stroke and stiffness of the same muscle can be changed to adapt to different environments. This research result may be applied to the robot actuation, which can adjust the dynamic performance of the muscle actuation and make the robot work in flexible motion modes.